Uniformity of microbial injection for reinforcing saturated calcareous sand: A multi-test approach - Xinlei Zhang; Yue Sun; Yumin Chen; Lu Liu; Wenwen Li; Yi Han (Biogeotechnics)
The mineralization process of microbial-induced calcium carbonate precipitation (MICP) is influenced by many factors, and the uniformity of the calcium carbonate precipitation has become the main focus and challenge for MICP technology. In this study, the uniformity of the saturated calcareous sand treated with MICP was investigated through one-dimensional calcareous sand column tests and model tests. The coefficient of variation was employed in one-dimensional sand column tests to investigate the impact of injection rate, cementation solution concentration, and number of injection cycles on the uniformity of the MICP treatment. Additionally, model tests were conducted to investigate the impact of injection pressure and methods on the treatment range and uniformity under three-dimensional seepage conditions. Test results demonstrate that the reinforcement strength and uniformity are significantly influenced by the injection rate of the cementation solution, with a rate of 3 mL/min, yielding a favorable treatment effect. Excessive concentration of the cementation solution can lead to significant non-uniformity and a reduction in the compressive strength of MICP-treated samples. Conversely, excessively low concentrations may result in decreased bonding efficiency. Among the four considered concentrations, 0.5 mol/L and 1 mol/L exhibit superior reinforcing effects. The morphological development of calcareous sandy foundation reinforcement is associated with the spatial distribution pattern of the bacterial solution, exhibiting a relatively larger reinforcement area in proximity to the lower region of the model and a gradually decreasing range towards the upper part. Under three-dimensional seepage conditions, in addition to the non-uniform radial cementation along the injection pipe, there is also vertical heterogeneity of cementation along the length of the injection pipe due to gravitational effects, resulting in preferential deposition of calcium carbonate at the lower section. The application of injection pressure and a double-pipe circulation injection method can mitigate the accumulation of bacterial solution and cementation solution at the bottom, thereby improving the reinforcement range and uniformity.